Uptake and metabolism of circulating chylomicron triglyceride by rabbit aorta - Alan Vost (Journal of Lipid Research, 1972)
To determine if chylomicron triglycerides are taken up and metabolized by the arterial wall, rabbit abdominal aortas were perfused in situ for various times up to 2 hr with blood–buffer containing isotopically labeled substrates. Labeled chylomicrons were obtained by feeding [3H]palmitic acid or [3H]glyceryl trioleate to rats and rabbits with cannulated thoracic ducts. After aortic perfusion with these chylomicrons, more than 85% of aortic lipid ester radioactivity was in triglyceride; when labeled glycerol or palmitic acid was perfused, most aortic ester lipid radioactivity was in diglycerides and phospholipids. This indicated that, during perfusion with chylomicrons, intact triglyceride molecules were taken up by aorta. The rate of triglyceride fatty acid uptake by the inner avascular segment approached maximal values at low concentrations of perfusate triglyceride fatty acids (2 mm), whereas uptake in the outer capillary perfused segment increased with increasing triglyceride fatty acid concentration (0.4–25 mm). By double-radioisotope techniques it was shown that aortic free fatty acid was derived from both perfusate free fatty acids and from hydrolysis of lipoprotein glycerides within the aortic wall. Uptake of chylomicron triglyceride by perfused aorta was independent of triglyceride hydrolysis, which was quantitatively small.